2012
DOI: 10.1007/s00410-011-0715-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of compaction and compositional convection during mafic crystal mush solidification: the Sept Iles layered intrusion, Canada

Abstract: Adcumulate formation in mafic layered intrusions is attributed either to gravity-driven compaction, which expels the intercumulus melt out of the crystal matrix, or to compositional convection, which maintains the intercumulus liquid at a constant composition through liquid exchange with the main magma body. These processes are length-scale and time-scale dependent, and application of experimentally derived theoretical formulations to magma chambers is not straightforward. New data from the Sept Iles layered i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 98 publications
2
7
0
Order By: Relevance
“…For a given compaction length δ c , the characteristic timescale τ 0 is the time required to reduce the porosity of the compacting layer by a factor of e (i.e., from Φ to Φ/ 2.718; McKenzie, ; Tegner et al, ): τ0=δc/ω0()1Φ Melting experiments on tholeiitic basalt revealed that 40% crystallization can form the crystal mush with the compressive strength large enough to experience compaction (Philpotts & Carroll, ). Experimental simulations revealed that the trapped melt fraction of crystal framework after gravitational settling of minerals is about 52%–54% in basaltic magma (Manoochehri & Schmidt, ; Schmidt et al, ), which agrees with the value of ~60% from both theoretical estimations and field measurements (Namur & Charlier, ; Shirley, ; Tegner et al, ). Core samples from the borehole PYZK38‐3 show the adcumulate texture with 3%–7% interstitial melt (Yao et al, ).…”
Section: Compaction Process Of the Poyi Intrusionsupporting
confidence: 72%
See 1 more Smart Citation
“…For a given compaction length δ c , the characteristic timescale τ 0 is the time required to reduce the porosity of the compacting layer by a factor of e (i.e., from Φ to Φ/ 2.718; McKenzie, ; Tegner et al, ): τ0=δc/ω0()1Φ Melting experiments on tholeiitic basalt revealed that 40% crystallization can form the crystal mush with the compressive strength large enough to experience compaction (Philpotts & Carroll, ). Experimental simulations revealed that the trapped melt fraction of crystal framework after gravitational settling of minerals is about 52%–54% in basaltic magma (Manoochehri & Schmidt, ; Schmidt et al, ), which agrees with the value of ~60% from both theoretical estimations and field measurements (Namur & Charlier, ; Shirley, ; Tegner et al, ). Core samples from the borehole PYZK38‐3 show the adcumulate texture with 3%–7% interstitial melt (Yao et al, ).…”
Section: Compaction Process Of the Poyi Intrusionsupporting
confidence: 72%
“…The weak fabric strength of olivine and clinopyroxene in the Poyi peridotites excludes the existence of magmatic currents or shearing of unconsolidated cumulates as observed in the Oman ophiolites (Boudier & Nicolas, ; Nicolas et al, ). Namur and Charlier () found that the compositional convection in the mafic crystal mush of the Sept Iles layered intrusion was triggered by the sudden drop of interstitial melt density due to the Fe‐Ti oxide saturation. Cu‐Ni sulfide deposits occur in the upper part of the dunite unit of the Poyi intrusion, indicating that saturation of sulfide minerals did not cause effective compositional convection in the Poyi parent magma (Yao et al, ).…”
Section: Compaction Process Of the Poyi Intrusionmentioning
confidence: 99%
“…Plagioclase with magmatic step-zoning is, however, also rel-atively common in some mafic igneous cumulates (Humphreys, 2009;Namur and Charlier, 2012;Namur et al, 2014). In these cumulates, part of the plagioclase crystals have largely unzoned cores, which are surrounded by a mantle with decreasing anor-thite content, followed by an overgrowth of constant low-anorthite composition with widths of up to several hundred micrometers.…”
Section: The Role Of Fractionation and Cumulate Formation In The Jiuzhou Magma Systemmentioning
confidence: 99%
“…Namur et al, 2014). The unzoned overgrowths may reflect postcumulus growth of interstitial melt during continuous convec-tive melt exchange with a large, evolved melt reservoir (Namur and Charlier, 2012) or crystallization at decreasing undercooling buffered by latent heat release (Namur et al, 2014).…”
Section: The Role Of Fractionation and Cumulate Formation In The Jiuzhou Magma Systemmentioning
confidence: 99%
“…However, pure orthocumulates are rare in nature because the initial crystal mushes evolve due to secondary or postcumulus processes (e.g., Campbell 1996;Hunter 1996b;McBirney et al 2009;Sparks et al 1985) toward mesocumulates (7-25 % interstitial melt) or adcumulates (0-7 % interstitial melt) (Irvine 1982;Wager et al 1960). Compaction is considered as one of the most effective postcumulus processes leading to the expulsion of interstitial melt out of the cumulate framework (e.g., Boorman et al 2004;Boudreau and Philpotts 2002;Mathez et al 1997;McBirney 1995;McKenzie 1984McKenzie , 2011Meurer and Boudreau 1998;Namur and Charlier 2012;Philpotts et al 1996;Shirley 1987;Sparks et al 1985;Tegner et al 2009). This process may initiate with a purely mechanical reorganization of crystals (slippage, rotation or bending) and continues with viscous deformation or creep of grains in the solid state which results in pressure dissolution/reprecipitation at the grain contacts and boundaries (i.e., viscous or chemical compaction) (e.g., Fowler and Yang 1999;Hunter 1996b).…”
Section: Introductionmentioning
confidence: 99%